2021
DOI: 10.25115/eea.v38i4.4041
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth In The Conditions Of Digitalization In The EU Countries

Abstract: The article discusses the dynamics of economic development based on the level of digitalization of the countries. Economic development is evaluated through the dynamics of GDP changes. Digitalization level is evaluated through the Digital Economy and Society Index (DESI), which is calculated on a regular basis by the European Commission. Object of study – 28 EU‑member countries. The hypothesis of the investigation: a high level of digitalization leads to an acceleration of economic growth on national level. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Pélaez et al [78] contrasted the digital skills of British youth with the expectations of the labour market and argued that the digital divide between the two could only be bridged through education and digital skills development. Kwilinski et al [79] found that the higher the level of digitalization in a society, the lower the risk of poverty and social exclusion Vyshnevskyi et al [80] points out by assessing the development of the EU economy through the dynamics of GDP change, that the dig-italization of the economy does not play a decisive role in the rate of economic growth achieved, given the current state of development of the technologies and institutions used. Our analysis shows that the Member States with the highest real GDP per capita have the highest digital readiness of human capital and internet services.…”
Section: Discussionmentioning
confidence: 99%
“…Pélaez et al [78] contrasted the digital skills of British youth with the expectations of the labour market and argued that the digital divide between the two could only be bridged through education and digital skills development. Kwilinski et al [79] found that the higher the level of digitalization in a society, the lower the risk of poverty and social exclusion Vyshnevskyi et al [80] points out by assessing the development of the EU economy through the dynamics of GDP change, that the dig-italization of the economy does not play a decisive role in the rate of economic growth achieved, given the current state of development of the technologies and institutions used. Our analysis shows that the Member States with the highest real GDP per capita have the highest digital readiness of human capital and internet services.…”
Section: Discussionmentioning
confidence: 99%
“…The development of investment-innovative business is formed on the basis of assessment and analysis of its real and potential technological level, modern IT-systems, customer analytics, number of business processes, knowledge-intensive products, increasing the level of innovation culture aimed at commercializing accumulated knowledge in ensuring increased competitiveness. Digitization of investment-innovative activities of business reflects a complex dynamic intensive development of business entities, which is quantitatively characterized by the ratio of changes in the effectiveness of their interaction in various sectors of the economy and the rate of change of resource costs involved in investment-innovative process (Davymuk et al, 2016;Vyshnevskyi et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…As part of the digital transition to the development of the national economy, many normative acts have been adopted (Kwilinski et al, 2020;Rovňák et al, 2022) and comprehensive studies are being carried out (Vyshnevskyi et al, 2019;Orbik and Zozulakova, 2019;Vyshnevskyi et al, 2020;Albu and Albu, 2021;Kurniawan et al, 2022;Ma and Zhu, 2022;Ozturk and Ullah, 2022;Purnomo et al, 2022;Reza-Gharehbagh et al, 2022;Yang et al, 2022;Zhou et al, 2022;Orzeł and Wolniak, 2022;Brodny and Tutak, 2022;Mynenko and Lyulyov, 2022;Mańka-Szulik and Krawczyk, 2022; The situation is the same with the second trendthe transition to a green economy (European Commission, 2019;Kwilinski et al, 2019;Kuzior et al, 2019;Kuzior et al, 2021;Dźwigoł et al, 2021;Dzwigol et al, 2021;Astawa et al, 2021;Midor, 2022, Deja et al 2019. These questions are often examined simultaneously in many studies (Bonire and Gbenga-Ilori, 2021;Stoican and Chirieac, 2021;Li, Liu and Ni, 2021;Nham and Ha, 2022;Li and Wang, 2022;Zhang et al, 2022a;Zhang et al, 2022b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To estimate digital economy level is used the Digital Economy and Society Index (hereinafter "DESI"). As have shown in previous analysis DESI more relevant for member countries EU-27 than the ICT Development Index, The Digital Adoption Index and others indexes, which describes process of economy digitalization (Vyshnevskyi et al, 2020). And only DESI is calculated specifically for the EU countries.…”
mentioning
confidence: 91%
See 1 more Smart Citation